A Comparative Analysis between Conventional Manufacturing and Additive Manufacturing of Ankle-Foot Orthosis - Shahar, Farah Syazwani; Hameed Sultan, Mohamed Thariq; Md Shah, Ain Umaira; Azrie Safri, Syafiqah Nur (Applied Science and Engineering Progress, 2020)
3D printing has been attracting attention in recent years due to its versatility in design optimization and reduced labour and production costs. It has been implemented in many major sectors such as automotive, aerospace, and healthcare. One of the most recent researches involving this technology is in the prosthetics and orthotics field. The aim of this paper is to review the recent researches on Ankle-Foot Orthosis (AFO) which uses 3D printing in its manufacturing and fabrication phase. This paper discusses the current 3D printing technologies used for AFO, the comparison between Conventional Manufacturing (CM) and Additive Manufacturing (AM) of AFO, as well as the mechanical properties of AFO prototypes built from 3D printing. Results from this review show that most current researches use Fused Deposition Modelling (FDM) or Selective Laser Sintering (SLS) for AFO manufacturing, and the materials used are mostly thermoplastics such as Nylon and Polyamide (PA). The results also show that the tensile strength and Young’s Modulus of a 3D-printed AFO could reach as high as 43 MPa and 3.9 GPa, respectively. It can be concluded that 3D printing provides wider opportunities in the development of AFO due to its versatility in optimizing complex geometries, time and weight savings, as well as its cost-effectiveness.